2021
DOI: 10.3389/fmicb.2021.604999
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting of Soil-Derived Actinobacteria Along the Alar-Hotan Desert Highway in the Taklamakan Desert

Abstract: Taklamakan desert is known as the largest dunefield in China and as the second largest shifting sand desert in the world. Although with long history and glorious culture, the Taklamakan desert remains largely unexplored and numerous microorganisms have not been harvested in culture or taxonomically identified yet. The main objective of this study is to explore the diversity, novelty, and pharmacological potential of the cultivable actinomycetes from soil samples at various sites along the Alar-Hotan desert hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 143 publications
(166 reference statements)
0
10
1
Order By: Relevance
“…This study revealed that Firmicutes, followed by Proteobacteria, are the most dominant phylum in Moroccan desert soils. These divisions have been observed in different hot deserts of the Tanami Desert, the Eastern Desert, and the Saudi Arabia Desert [36] , While Actinobacteria phyla was less prevalent Contrary to other studies conducted in similar locations in the Atacama Desert, Namib Desert, and Thar Desert [37] [40] . These findings indicate that these phyla have adapted effectively to the scorching desert environment.…”
Section: Discussioncontrasting
confidence: 58%
“…This study revealed that Firmicutes, followed by Proteobacteria, are the most dominant phylum in Moroccan desert soils. These divisions have been observed in different hot deserts of the Tanami Desert, the Eastern Desert, and the Saudi Arabia Desert [36] , While Actinobacteria phyla was less prevalent Contrary to other studies conducted in similar locations in the Atacama Desert, Namib Desert, and Thar Desert [37] [40] . These findings indicate that these phyla have adapted effectively to the scorching desert environment.…”
Section: Discussioncontrasting
confidence: 58%
“…Among these isolates, Streptomyces (20 strains), Nesterenkonia (13 strains) and Kocuria (4 strains) were the most abundant genera. Genera Streptomyces , Kocuria , Nesterenkonia , Nocardiopsis , Haloactinobacterium , Saccharopolyspora , Actinopolyspora , et al are often reported as halotolerant or halophilic actinobacteria found in salty desert environment [ 77 ]. Herein genera obtained from high-salts media agree with the previous studies on population composition of actinobacteria in different saline or hypersaline habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, multi-membered colour-groups encompassing isolates from the northern slope of the pine forest were equated with the genera Actinacidiphila, Catenulispora, Kitasatospora, Pilimelia, Streptacidiphilus, and Streptomyces. Corresponding multi-membered colour-groups composed of isolates from the southern slope of the pine forest were either equated with the genera Actinacidiphila, Actinospica, Nocardia, and Streptomyces or were close to or bona fide members of Pilimelia columellifera subspecies pallida (Vobis et al, 1986) and Streptomyces celluloflavus (Nishimura et al, 1953) Madhaiyan et al, 2020. These data provide further evidence that 16S rRNA gene sequencing remains a practical way of determining the taxonomic status of filamentous actinomycetes isolated from extreme habitats (Goodfellow et al, 2018;Singh and Dubey, 2018;Sharma and Thakur, 2020;Liu et al, 2021).…”
Section: Colour-group Assignment Dereplication Of Isolates and Phylogenymentioning
confidence: 97%
“…The taxonomic data acquired in this study show that selective isolation, dereplication and initial characterization of representative isolates from diverse extreme biomes is a simple and practical way of selecting putatively novel and rare filamentous actinomycetes for exploitative biotechnology. In addition, these data underpin the rational of ecologically guided bioprospecting campaigns featuring actinomycetes (Mitra et al, 2011;Nalini and Prakash, 2017;Liu et al, 2021;Wang et al, 2022). Many of the isolates found to belong to rare and putatively novel taxa were from the litter and mineral horizons of the pine forest indicating that acidophilic and acidotolerant filamentous actinomycetes should feature more prominently in the search for novel bioactive compounds, especially given evidence that such strains are a source of novel antibiotics and acid-stable enzymes (Golińska et al, 2023).…”
Section: Colour-group Assignment Dereplication Of Isolates and Phylogenymentioning
confidence: 99%